Examining Gender Roles and Professional Realities: Stereotypes Against Women in Islamic Societies - Nadirra, Trie; Nadilla, Trie (Saree: Research in Gender Studies, 2023)
Women have long been a topic of discussion throughout history. There are numerous questions and issues surrounding women's existence, particularly their rights and roles as members of society. Discussions frequently revolve around women's professional careers. In this paper, we will examine women's roles in the workplace, as well as their positions in various religions prior to the emergence of Islam. This study aims to determine Islamic perspectives on the career woman stereotype. This study utilized a literature review, citing primary sources such as the Qur'an, Hadis, fiqh books, scientific journals, and relevant social works. Women are allowed to work in Islam as long as they follow sharia. Women are categorized as God's servants and may contribute to society in a variety of ways. In practice, many women decide to work to help their husbands with family responsibilities. The Qur'an teaches that all believers, men and women, are equal before Allah. As a result, they should have equal standing in regards to God, and they have both been declared equal in their ability to receive His grace. As a result, women face no barriers to employment as long as the work is done in a respectful and polite environment, and they can practice their religion without negatively impacting themselves or the environment.   Abstrak Sepanjang sejarah perdaban Islam, perempuan telah menjadi subjek perdebatan. Keberadaan wanita menimbulkan banyak pertanyaan dan masalah, terutama hak dan peran mereka sebagai anggota masyarakat. Dunia kerja perempuan sering menjadi subjek diskusi. Kami akan membahas peran perempuan sebelum kedatangan Islam di tempat kerja dan dalam berbagai agama. Tujuan dari penelitian ini adalah untuk mengetahui pandangan Islam tentang stereotip yang dimiliki wanita karir. Sumber-sumber penting seperti Al-Qur'an, Hadis, kitab-kitab fikih, jurnal ilmiah, dan karya-karya sosial yang relevan dikutip dalam penelitian ini. Tinjauan literatur juga digunakan. Dalam Islam, perempuan yang mengikuti syariah dapat bekerja. Perempuan adalah hamba Allah dan dapat membantu masyarakat dengan berbagai cara. Pada kenyataannya, banyak perempuan yang memilih untuk bekerja untuk membantu suami mereka menyelesaikan tugas keluarga. Al-Qur'an menyatakan bahwa semua orang beriman adalah setara di hadapan Allah, jadi mereka berdua harus memiliki kedudukan yang sama di hadapan-Nya dan memiliki kemampuan untuk menerima anugerah-Nya. Akibatnya, perempuan tidak menghadapi kesulitan untuk bekerja selama pekerjaan itu dilakukan dalam lingkungan yang sopan dan terhormat, dan mereka dapat mempraktikkan agama mereka tanpa berdampak negatif terhadap diri mereka sendiri atau lingkungan